Pengaruh Pembelajaran Tematik Terpadu melalui Metode Bermain Peran terhadap Pemahaman Budaya Osing Siswa Kelas IV SDN 4 Gambiran Banyuwangi - Rima Trianingsih (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2017)
Education in Banyuwangi have declared bahasa Osing as local content on learning at school. Such things as a step to keep preserving the Osing culture through education role. However, preliminary results of a study on the grade IV SDN 4 Gambiran on July 15, 2017 shows that comprehension of students against the Osing culture are still low. This research aims to know the influence of thematic integrated learning through of the role playing method againt the understanding Osing culture of the grade IV SDN 4 Gambiran, Banyuwangi. Can be obtained that the P value (Sig 2 tailed) for 0.000 smaller than 0.05 so that it can be concluded that there are significant differences between the average data group pre test (before treatment) and post data group test (after treatment). It can be concluded that the hypothesis stating